Cross-Species Y Chromosome Function Between Malaria Vectors of the Anopheles gambiae Species Complex. Issue 2 (31st August 2017) - Bernardini, Federica; Galizi, Roberto; Wunderlich, Mariana; Taxiarchi, Chrysanthi; Kranjc, Nace; Kyrou, Kyros; Hammond, Andrew; Nolan, Tony; Lawniczak, Mara N K; Papathanos, Philippos Aris; Crisanti, Andrea; Windbichler, Nikolai
Abstract: Y chromosome function, structure and evolution is poorly understood in many species, including the Anopheles genus of mosquitoes—an emerging model system for studying speciation that also represents the major vectors of malaria. While the Anopheline Y had previously been implicated in male mating behavior, recent data from the Anopheles gambiae complex suggests that, apart from the putative primary sex-determiner, no other genes are conserved on the Y. Studying the functional basis of the evolutionary divergence of the Y chromosome in the gambiae complex is complicated by complete F1 male hybrid sterility. Here, we used an F1 × F0 crossing scheme to overcome a severe bottleneck of male hybrid incompatibilities that enabled us to experimentally purify a genetically labeled A. gambiae Y chromosome in an A. arabiensis background. Whole genome sequencing (WGS) confirmed that the A. gambiae Y retained its original sequence content in the A. arabiensis genomic background. In contrast to comparable experiments in Drosophila, we find that the presence of a heterospecific Y chromosome has no significant effect on the expression of A. arabiensis genes, and transcriptional differences can be explained almost exclusively as a direct consequence of transcripts arising from sequence elements present on the A. gambiae Y chromosome itself. We find that Y hybrids show no obvious fertility defects, and no substantial reduction in male competitiveness. Our results demonstrate that, despite their radically different structure, Y chromosomes of these two species of the gambiae complex that diverged an estimated 1.85 MYA function interchangeably, thus indicating that the Y chromosome does not harbor loci contributing to hybrid incompatibility. Therefore, Y chromosome gene flow between members of the gambiae complex is possible even at their current level of divergence. Importantly, this also suggests that malaria control interventions based on sex-distorting Y drive would be transferable, whether intentionally or contingent, between the major malaria vector species.